The dawn of religious pluralism : voices from the World's Parliament of Religions, 1893 - World's Parliament of Religions (1893 : Chicago, Ill.); Seager, Richard Hughes; Council for a Parliament of the World's Religions (1993)
On September 11th, 1893, the Columbian Liberty Bell at the World's Columbian Exposition in Chicago sounded ten times, symbolizing what were then considered the ten great religious traditions: Hinduism, Buddhism, Jainism, Zoroastrianism, Taoism, Confucianism, Shintoism, Judaism, Christianity, and Islam. One of the most significant events in American religious and cultural history had begun. The ochre robes of Buddhist ascetics, the vermilion cloaks and turbans of Hindu swamis, the silk vestments of Confucians, Taoists, and Shinto priests, the somber garb of Protestant ministers, all gathered together on the platform around a Roman Catholic cardinal, dressed in scarlet and seated in a high chair of state. The near-ecstatic crowd repeatedly burst into tumultuous applause, waving handkerchiefs, and mingling tears with smiles. Nothing like the World's Parliament of Religions had been seen in the history of the world, and nothing like it was to be seen again for many years: a gathering of representatives of numerous world religions for an exchange of views. It was a turning point in American life, presaging the multiculturalism of a century later. This volume contains a selection of 60 representative and revealing addresses given to the Parliament, with authoritative introductions and notes by Professor Seager. The addresses include contributions by Protestant mainstream ministers, African-Americans, Roman Catholics, Orthodox Christians, Jews, Muslims, Buddhists, Hindus, and representatives of other Asian religions. Also included are various "points of contact and contention," in which religious leaders attempted to analyze or reach out to their counterparts in other traditions
Evolution and Christianity / Henry Drummond -- Science a religious revelation / Paul Carus -- Christianity as seen by a voyage around the World / Francis Edward Clark -- The invincible Gospel / George F. Pentecost -- The attitude of Christianity to other religions / William C. Wilkinson -- The religion of the future / John Talbot Gracey -- The bearing of religious unity on the work of the Christian missions / George T. Candlin -- Orthodox or historical Judaism / Henry Pereira Mendes -- Criticism and discussion of missionary methods / Narasima Charya -- Impromptu comments / Virchand Gandhi -- Impromptu comments / Vivekananda -- The work of social reform in India / B.B. Nagarkar -- Confucianism / Pung Kwang Yu
"Published in association with the Council for a Parliament of the World's Religions."
Includes bibliographical references and index
Keywords: Religions -- Congresses; Religions -- Relations -- Congresses; Religions -- Congresses; Religions -- Relations -- Congresses; Conference proceedings